An integrated change management model for digital transformation in Colombia’s pipeline sector - Rosero-Garcia, Javier; Sanchez, Jon Freddy Hernandez; Montano-Salamanca, William (International Journal of Management and Sustainability, 2026)
The present study proposes a methodology for managing organizational change amid digital transformation within Colombia’s hydrocarbon pipeline sector. The model is employed to analyze established organizational change models, with subsequent adaptation and validation for the specific needs of the pipeline industry. In-depth interviews with industry experts were conducted, digital maturity questionnaires administered, and a case study carried out on two pipelines with different operational characteristics. Data analysis incorporated thematic analysis, concordance coefficient evaluation, and word cloud creation to identify emerging themes. The resultant model, designated the Integrated Organizational Change Model (IOCM), comprises four phases: I) diagnosis and preparation; II) collaborative design; III) agile implementation; and IV) reinforcement and evolution. The model incorporates agile methodologies, design thinking, and socio-technical approaches tailored to the needs of the pipeline sector. The IOCM was evaluated by experts, who assigned high ratings for its structure and adaptability, with most components scoring above 4.5 on a 5-point Likert scale. The organization’s key strengths identified include digital maturity assessment, socio-technical strategy development, and a focus on continuous improvement. However, the study also identified areas for enhancement, including the necessity to place greater emphasis on financial aspects and to improve the model’s adaptability to organizations of diverse sizes. The following recommendations are proposed for future research: longitudinal studies and the integration of emerging technologies into the model.